A digital pragmatics inquiry: Academic performance and transformative awareness in Saudi EFL online environments - Alhumsi, Mohammad Husam; Almehmadi, Wesam (English Language Teaching Educational Journal, 2025)
Pragmatic competence is essential for communicative competence, yet under-researched in Saudi EFL contexts, particularly within the post-pandemic shift to digital instruction. This study investigates online learning as a transformative site for pragmatic development, examining Saudi EFL undergraduates’ pragmatic awareness within this digital context and the influence of gender, age, and GPA. A quantitative design utilized an online questionnaire with authentic scenarios. Data from 138 students, analyzed via t-tests and ANOVA, revealed that most students perceived the online environment as beneficial for developing pragmatic awareness. Participants demonstrated notable competence in specific digital interactions. While no significant differences were found based on gender or age, GPA emerged as a key factor. This study contributes to digital pragmatics research by empirically positioning the post-pandemic online classroom as a viable space for metapragmatic development, not merely a compensatory tool. It challenges demographic assumptions, highlighting academic profile as a primary differentiator in this new learning ecology. Pedagogically, it argues for intentionally leveraging online platforms to design targeted, authentic pragmatic practice for diverse learners.